Characterization of research in a Brazilian institution of education, science and technology: trajectory and predominance of thematic areas (Research, Society and Development, 2022)
The study is intended to portray, through descriptive research in document analysis, the scientific production of the Araçuaí Campus of the Instituto Federal do Norte de Minas Gerais-IFNMG, in the interstice from 2014 to 2020. In the period, a mapping of the research projects developed on campus through support notices and on a voluntary basis, and characterization and analysis were carried out. The analyzes were guided by the following questions: Quantitative and oscillations of research projects, from different thematic areas; Search types; Gender contributions to research; Qualification level of researchers; Matrix of Strengths, Weaknesses, Opportunities and Threats in the IFNMG Research – Araçuaí Campus according to thematic areas. As a result, there is an inclination of production concentrated in sub-areas of the human sciences, as well as the agricultural sciences. From the analysis, it is concluded that there is a need to adapt the research efforts of the campus and a plurality of areas of knowledge in the formation of the faculty, in addition to proximity to regional specificities. It is necessary to expand the dissemination of local scientific production in the said areas of knowledge, adjusted to the Institutional Development Plan (PDI) of the campus and data for the discussion of public policies and regional development.